Pasture and grassland productivity and foliar elongation of wheatgrass in Southern Patagonia = Productividad de pastura y pastizal y elongación foliar de agropiros en la Patagonia austral = Produtividade pastagem e pasto natural e alongamento foliar de agropyros no Sul da Patagônia - Utrilla, Victor Ricardo; Andrade, Miguel Alberto; Vargas, Paola Patricia; Alsina, María Luz; Aguilar, Romina; Galván, Julieta (INIA Uruguay y Facultad de Agronomía, Universidad de la República, 2023)
The aim of this work was to show the relationship of the productivity of a pasture and grassland, the living and dead material, and the foliar elongation of wheatgrass with the soil moisture and the thermal sum in Southern Patagonia (Argentina). During the years 2015/16 (Year 1) and 2016/17 (Year 2), in closures excluded from grazing, the plant height, the accumulated aerial biomass (AAB) and the daily growth rate (DGR) of a mixed pasture and grassland were determined monthly from October to February. The forage harvested from the pasture was characterized in live (LM) and dead material (DM), and the live AAB was calculated. In selected wheatgrass plants, the leaf elongation rate (LER) was determined. Soil moisture (SM) was measured and the thermal sum (TS) was calculated. The AAB was analyzed using a factorial arrangement in a completely randomized design. The results were subjected to ANVA with repeated measures analysis and the means were adjusted with the Tukey-Kramer test. DGR, LM, and LER were related to SM and TS by multiple regression analysis. In both Year 1 and Year 2 and same months the AAB of the pasture exceeded the forage accumulated by the grassland. The LM and the LER varied according to the changes in the SM, and the TS explained the variations of the parameters described, which should be considered when developing future management strategies in this type of pasture.